Über einen nicht-holonomen Komplex - Grincevičius, K. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. И. Гринцевичюс. О неголономном комплексеK. Grincevičius. Apie neholonominį kompleksą